The SCUBA-2 Cosmology Legacy Survey: multiwavelength counterparts to 103 submillimeter galaxies in the UKIDSS-UDS field - Chen, Chian-Chou; Smail, Ian; Ivison, Rob J.; Arumugam, Vinodiran; Almaini, Omar; Conselice, Christopher J.; Geach, James E.; Hartley, Will G.; Ma, Cheng-Jiun; Mortlock, Alice; Simpson, Chris; Simpson, James M.; et al. (American Astronomical Society, 2016)
We present multiwavelength identifications for the counterparts of 1088 submillimeter sources detected at 850 μm in the SCUBA-2 Cosmology Legacy Survey study of the UKIRT Infrared Deep Sky Survey-Ultra-Deep Survey (UDS) field. By utilizing an Atacama Large Millimeter Array (ALMA) pilot study on a subset of our bright SCUBA-2 sample as a training set, along with the deep optical–near-infrared (OIR) data available in this field, we develop a novel technique, Optical–IR Triple Color (OIRTC), using z − K, K − [3.6], [3.6] − [4.5] colors to select the candidate submillimeter galaxy (SMG) counterparts. By combining radio identification and the OIRTC technique, we find counterpart candidates for 80% of the Class = 1 ≥ 4σ SCUBA-2 sample, defined as those that are covered by both radio and OIR imaging and the base sample for our scientific analyses. Based on the ALMA training set, we expect the accuracy of these identifications to be 82% ± 20%, with a completeness of 69% ± 16%, essentially as accurate as the traditional p-value technique but with higher completeness. We find that the fraction of SCUBA-2 sources having candidate counterparts is lower for fainter 850 μm sources, and we argue that for follow-up observations sensitive to SMGs with S850 gsim 1 mJy across the whole ALMA beam, the fraction with multiple counterparts is likely to be >40% for SCUBA-2 sources at S850 gsim 4 mJy. We find that the photometric redshift distribution for the SMGs is well fit by a lognormal distribution, with a median redshift of z = 2.3 ± 0.1. After accounting for the sources without any radio and/or OIRTC counterpart, we estimate the median redshift to be z = 2.6 ± 0.1 for SMGs with S850 > 1 mJy. We also use this new large sample to study the clustering of SMGs and the far-infrared properties of the unidentified submillimeter sources by stacking their Herschel SPIRE far-infrared emission.